2000
DOI: 10.1063/1.126095
|View full text |Cite
|
Sign up to set email alerts
|

Adatom condensation and quantum dot sizes in InGaAs/GaAs (001)

Abstract: Articles you may be interested in Atomic structure and stoichiometry of In(Ga)As/GaAs quantum dots grown on an exact-oriented GaP/Si (001)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…The SAQD formed under higher AsH 3 partial pressures had lower densities than the ones grown under low partial pressure conditions [17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SAQD formed under higher AsH 3 partial pressures had lower densities than the ones grown under low partial pressure conditions [17].…”
Section: Resultsmentioning
confidence: 99%
“…6 As under different AsH 3 partial pressures and different growth temperatures. Lower growth temperatures have been identified previously as reducing surface segregation [11,12], but the role of AsH 3 on QD formation has only been speculated [16,17]. Conditions where surface segregation is suppressed and enhanced are identified.…”
Section: Growth Investigations On Ingaas Alloy Saqdmentioning
confidence: 97%
“…Some of these studies have already shown significant differences in size, shape and composition between uncapped and capped QDs. For example, an important collapse of the QD height has been reported for InAs/GaAs QDs capped with GaAs [14,15,[17][18][19], revealing the big influence of the capping process on the structural properties of the QDs.…”
Section: Capping Process Of Inas Quantum Dotsmentioning
confidence: 99%
“…Nevertheless, once created, the QDs are subsequently capped, a step which is required for any device application. Although a lot of effort has been dedicated to understand the QD growth mechanism, there are relatively few studies focused on the effect of the capping process [12][13][14][15][16][17][18][19][20]. Some of these studies have already shown significant differences in size, shape and composition between uncapped and capped QDs.…”
Section: Capping Process Of Inas Quantum Dotsmentioning
confidence: 99%
See 1 more Smart Citation